Speaking personally : - Ladousse, Gillian Porter (Cambridge University Press, 1989)
This book is a collection of absorbing and thought-provoking questionnaires and quizzes with related activities for students of English at upper-intermediate and more advanced levels. Questions requiring a personal response from the reader can serve as an enjoyable and provocative starting-point for fluency practice in the language classroom. The book is designed for use in the classroom, but much of the material can be used by students working alone. Those sections best suited to the individual reader are indicated by a special symbol in the text. At the end of the book both teachers and students will find guidelines on how to work through the units. A chart is also included to show how the activities can link up with main course work